(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
Many of the polyherbal formulations are described in ayurvedic classics for inflammation and pains. Among them rasna saptak kwath gives best therapeutic effect in clinical studies but palatable issue makes it less popular among patients. The present work emphasizes on the transformation of this classical formulation into more convenient and acceptable form for the patients without disturbing its efficacy. In the present study kwath was converted into mechanical spray form for pain and inflammation. The extractions of herbs were done by both classical and modern methods. The mechanical spray solution was prepared with permeation enhancer, humectant, in suitable solvent system. The spray was standardized on various parameters like viscosity, evaporation time, and spray pattern. Spray was also evaluated for in vitro drug release, anti inflammatory, analgesic and skin irritation study. In the result, the spray pattern was found uniform and evaporation time was 9.81±0.30 min. The fluxes for spray were found to be 2.82±.0.11 (µg/cm2/h). The kinetic model for spray best fitted to zero order permeation at a constant flux for spray r>0.98. The spray also provides good results in pain and inflammation. So, here is the possibility of replacing that sticky oil of Ayurveda with spray for good relief. The products show the path for a new generation of Ayurvedic dosage form, which has the bright future in this busy schedule of life where integrity of Ayurvedic medicines not hampered.